FAKTOR YANG BERHUBUNGAN DENGAN CAKUPAN PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) DI KOTA KENDARI: Factors Connected With Coverage Of Visual Infection Of Acetic Acid Inspection (Iva) In Kendari City - Asni Jaya (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
Currently the scope for early detection of cervical cancer in Kendari through examination of infection visually acid asesat (IVA) is still very low (around 5%), whereas coverage early detection are effective in reducing morbidity and angk deaths due to cervical cancer is 85%. The purpose of this study was to determine the factors associated with infection visual inspection coverage acetic acid (VIA) in Kendari. This type of research is quantitative with case control design. The population in this study, divided into two populations is the case of reproductive age women who had had early detection of cervical cancer in Kendari as many as 606 people, while the population control as much as 94 403 people. The sample size of each group were 83 respondents, who were taken by simple random sampling. Data were collected by questionnaire, and then analyzed by descriptive and inferential using Chi Square tes. The results showed that there is a relationship of knowledge with low coverage infection visual inspection of acetate acid (IVA) in Kendari, which gained value X2 count> X2 table (48.824> 3.841) .Terdapat relationship with a lower attitude coverage infection visual inspection of acetate acid (VIA) in Kendari, which gained value X2 count> X2 table (36.763> 3.841) .Terdapat husband support relationships with low coverage infection visual inspection of acetate acid (IVA) in Kendari, which gained value X2 count> X2 table (75.841> 3.841) .Terdapat relationships support healthcare workers with low coverage infection visual inspection of acetate acid (IVA) in Kendari.